Dualisme Pengaturan Hukum dalam Pengelolaan Tanah Desa di Daerah Istimewa Yogyakarta - Supama, Yohanes; Imbiri, Antonius (Tunas Agraria, 2025)
This study aims to examine the dualism of legal arrangements in village land management in the Special Region of Yogyakarta, particularly due to differences in norms between the Basic Agrarian Law and the Special Region of Yogyakarta Law. The main focus of the study is on the legal status of village land that was previously certified in the name of the village government but was later claimed as belonging to the sultanate or duchy based on the provisions of the special rights. This study uses a normative juridical method with a historical approach and regulatory comparison and examines the relationship between national regulations, regional regulations, and applicable legal principles. The results of the study indicate that there is a lack of synchronization in terms of the subject of rights, the status of rights, and the legalization mechanism for village land, which has an impact on legal uncertainty at the village level. In addition, the determination of the sultanate and duchy as the subjects of land ownership rights without a mechanism for releasing them from the village government is considered contrary to the principles of non-retroactivity and lex superior. The conclusion of this study is that regulatory harmonization is needed to ensure legal certainty and justice for village communities without ignoring the recognition of regional special rights.   Penelitian ini bertujuan untuk mengkaji persoalan dualisme pengaturan hukum dalam pengelolaan tanah desa di Daerah Istimewa Yogyakarta, khususnya akibat perbedaan norma antara Undang-Undang Pokok Agraria dan Undang-Undang Keistimewaan Daerah Istimewa Yogyakarta. Fokus utama kajian adalah pada status hukum tanah desa yang sebelumnya telah disertipikatkan atas nama pemerintah desa, namun kemudian diklaim sebagai milik Kasultanan atau Kadipaten berdasarkan ketentuan keistimewaan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan historis dan perbandingan peraturan, serta menelaah keterkaitan antara peraturan nasional, peraturan daerah, dan asas-asas hukum yang berlaku. Hasil penelitian menunjukkan bahwa terjadi ketidaksinkronan dalam hal subjek hak, status hak, dan mekanisme legalisasi tanah desa, yang berdampak pada ketidakpastian hukum di tingkat desa. Selain itu, penetapan Kasultanan dan Kadipaten sebagai subjek hak milik atas tanah tanpa mekanisme pelepasan hak dari pemerintah desa dinilai bertentangan dengan asas non-retroaktif dan prinsip lex superior. Kesimpulan dari penelitian ini adalah bahwa dibutuhkan harmonisasi regulasi yang menjamin kepastian hukum dan keadilan bagi masyarakat desa tanpa mengabaikan pengakuan terhadap keistimewaan daerah.